2020
DOI: 10.1007/s00412-020-00742-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background impacts the timing of synaptonemal complex breakdown in Drosophila melanogaster

Abstract: Experiments performed in different genetic backgrounds occasionally exhibit failure in experimental reproducibility. This is a serious issue in Drosophila where there are no standard control stocks. Here, we illustrate the importance of controlling genetic background by showing that the timing of a major meiotic event, the breakdown of the synaptonemal complex (SC), varies in different genetic backgrounds. We assessed SC breakdown in three different control stocks and found that in one control stock, y w; svsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…15,16 The Drosophila models of the bang sensitive (BS) family used in the study were the bang senseless or bss1 mutants of the paralytic gene (para bss1 ), 48,49 and the wild-type strains used as controls were Oregon-R or OrR and Canton-Special (CS). [49][50][51] Male flies were used as a previous laboratory study has shown differences between female and male bss Drosophila because the para bss is located on the X chromosome, and heterozygous para bss/+ female Drosophila have significantly decreased recovery times. 52 Only animals that underwent seizures were included in the study during behavioral (convulsion and learning/memory tests) and histological assessments.…”
Section: Animalsmentioning
confidence: 99%
“…15,16 The Drosophila models of the bang sensitive (BS) family used in the study were the bang senseless or bss1 mutants of the paralytic gene (para bss1 ), 48,49 and the wild-type strains used as controls were Oregon-R or OrR and Canton-Special (CS). [49][50][51] Male flies were used as a previous laboratory study has shown differences between female and male bss Drosophila because the para bss is located on the X chromosome, and heterozygous para bss/+ female Drosophila have significantly decreased recovery times. 52 Only animals that underwent seizures were included in the study during behavioral (convulsion and learning/memory tests) and histological assessments.…”
Section: Animalsmentioning
confidence: 99%
“…Therefore, SC defects serve as a proxy for premature loss of meiotic cohesion. In wild-type Drosophila oocytes, the SC fully assembles in germarial region 2A and usually remains intact until stages 5-6, although the timing of disassembly can be affected by genetic background [30,31]. To express lower levels of RNAi insensitive HA-tagged Smc3* specifically during prophase, we utilized a previously described weak mata-Gal4-VP16 driver chromosome [23].…”
Section: Sc Defects Caused By Prophase Knockdown Of Endogenous Smc3 P...mentioning
confidence: 99%